The evolution, ecology, and conservation of hummingbirds and their interactions with flowering plants - Leimberger, Kara G.; Dalsgaard, Bo; Tobias, Joseph A.; Wolf, Christopher; Betts, Matthew G. (Biological reviews of the Cambridge Philosophical Society, 2022)
ABSTRACT The ecological co‐dependency between plants and hummingbirds is a classic example of a mutualistic interaction: hummingbirds rely on floral nectar to fuel their rapid metabolisms, and more than 7000 plant species rely on hummingbirds for pollination. However, threats to hummingbirds are mounting, with 10% of 366 species considered globally threatened and 60% in decline. Despite the important ecological implications of these population declines, no recent review has examined plant–hummingbird interactions in the wider context of their evolution, ecology, and conservation. To provide this overview, we (i) assess the extent to which plants and hummingbirds have coevolved over millions of years, (ii) examine the mechanisms underlying plant–hummingbird interaction frequencies and hummingbird specialization, (iii) explore the factors driving the decline of hummingbird populations, and (iv) map out directions for future research and conservation. We find that, despite close associations between plants and hummingbirds, acquiring evidence for coevolution (versus one‐sided adaptation) is difficult because data on fitness outcomes for both partners are required. Thus, linking plant–hummingbird interactions to plant reproduction is not only a major avenue for future coevolutionary work, but also for studies of interaction networks, which rarely incorporate pollinator effectiveness. Nevertheless, over the past decade, a growing body of literature on plant–hummingbird networks suggests that hummingbirds form relationships with plants primarily based on overlapping phenologies and trait‐matching between bill length and flower length. On the other hand, species‐level specialization appears to depend primarily on local community context, such as hummingbird abundance and nectar availability. Finally, although hummingbirds are commonly viewed as resilient opportunists that thrive in brushy habitats, we find that range size and forest dependency are key predictors of hummingbird extinction risk. A critical direction for future research is to examine how potential stressors – such as habitat loss and fragmentation, climate change, and introduction of non‐native plants – may interact to affect hummingbirds and the plants they pollinate.